Designing a Problem-Based Model of Writing Development for Iranian EFL Learners - Hanieh Kashi; Shahram Afraz; Fazlolah Samimi (Iranian Journal of Applied Language Studies, 2022)
This study aimed at designing a problem-based model of writing development for Iranian EFL learners. To this end, a qualitative content analysis method was used. The participants included EFL teachers (N=10) and learners (N=15) with teaching and learning experience in writing courses at different language institutes of Iran. They were selected through purposive sampling. To collect the data, a semi-structured interview was used. More particularly, initially, the respondents in this study were interviewed to find out what their views about PBL is. The researchers began the qualitative data collection procedure and continued until data was saturated. The semi-structured questions administered to the respondents dealt with various aspects of PBL including: searching for answers, collaborative learning, cognitive thinking, learner-centered learning, diminished rule of the teacher, feedback dynamics in PBL, synthesis of data, and application of findings. By using the views of participants with regards to PBL, a new PBL model for the writing skill were designed. The findings can have implications for EFL teachers, learners, and curriculum planners.